Pengaruh Model Pembelajaran Problem Solving Berbasis HOTS Terhadap Minat dan Hasil Belajar Matematika Pada Siswa Jurusan Multimedia - Hukunala, Mozard Aryan (KAMBOTI: Jurnal Sosial dan Humaniora, 2022)
This study aims to determine the effect of the HOTS-based problem solving learning model on the interest and learning outcomes of mathematics in students majoring in multimedia. The process of learning mathematics in the multimedia department in the new normal period is still contextual and dominated by researchers (teaching flashlights). Students are often directed by researchers to memorize various definitions, theorems, theorems and formulas. This learning process causes students to tend to be bored and less interested in receiving lessons.This research is a quantitative descriptive study and was carried out in the multimedia department of SMK Negeri 6 Ambon with a total sample of 225 students consisting of class X multimedia 1, class X multimedia 2, class XI multimedia 1, class XI multimedia 2, class XII multimedia 1, class XII multimedia 2. Data collected through test, questionnaire, observation and documentation techniques were analyzed using descriptive analysis.The results of data analysis showed that interest in learning mathematics in multimedia majors from 44.7% to 72.4%, class XI from 50.6% to 78.5%, and class XII from 51.4% to 78.6%. Meanwhile, the achievement of learning outcomes using the HOTS-based problem solving learning model for class X with an average score of 89.13, class XI with an average value of 95.30 and class XII with an average value of 97.3 meet the KKM. These results conclude that the model of HOTS-based problem solving learning affects students' interest and learning outcomes in the multimedia department.